(untitled) (Jurnal Bahasa, 2023)
This study compares the differences between meN-...-i verbs and their Chinese equivalents in terms of their meanings and forms. The aim of this study is to highlight the differences between meN-...-i verbs and their equivalents, as well as the problems of dictionary use caused by the said differences. The bilingual dictionary that serves as the corpus of this study is Kamus Umum Bahasa Melayu-Cina Serba Baru (2015). This study employed Johansson’s theory of interlingual contrast (2008), Hartmann’s theory of lexicography (2001), as well as Nik Safiah et al.’s approach of Malay verbs and affixes (2015). The analysis of interlingual contrast of the meN-...-i verbs and their Chinese equivalents shows that the most noticeable difference is that the meN-...-i verbs have changes in forms and affixation, but they do not occur in their Chinese equivalents. This difference creates a problem in dictionary use, specifically in the comprehension of the meN-...-i verbs’ transitive functions and their grammatical meanings, as well as the objects accepted by meN-...-i verbs. The findings also indicate that the preparation of meN-...-i verbs’ equivalents in Malay-Chinese dictionaries involves the transfer of information that encompasses the meaning of the root word, the transitive functions, the grammatical meaning of the verb, and the object accepted by the meN-...-i verbs. Among the above-mentioned information, the transitive functions and grammatical meaning of meN-...-i are crucial aspects in producing effective translations in Malay-Chinese bilingual dictionaries. Keywords: meN-...-i verbs, interlingual contrast, equivalent, Malay-Chinese translation, bilingual dictionary use, lexicography Full text: PDF